Diagnostic Role of C- Reactive protein in Acute Appendicitis - Pun, Ashis; Dhungana, Amit; Bastola, Ramjee (Journal of College of Medical Sciences-Nepal, 2020)
Introduction: Acute appendicitis is the common surgical disease however, accurate diagnosis and exclusion of acute appendicitis always remains challenge to the surgeons. Although diagnoses rely mostly on clinical examination but C- reactive protein (CRP) can be of valuable armamentarium. Hence, this study was conducted to find the diagnostic role of C-reactive protein in Acute Appendicitis Methods: A retrospective cross sectional study was conducted among 100 respondents in the Department of Surgery, Bharatpur Hospital from September 2019 to August 2020. Ethical approval was taken from the Institutional Review Committee (IRC) Bharatpur Hospital. Statistical analysis was done by using SPSS version 16 using descriptive statistics. Results: Total of 100 patients was included in study with mean age 31 years old.Out of which 60% were male and 40% were female. CRP value was raised (>6) in 87 (87%) cases and normal in 13(13%) cases. Among those with raised CRP, three patients had normal appendix histopathologically and 57 had uncomplicated appendicitis and 27 had complicated appendicitis histopathologically with sensitivity, specificity, positive predictive value and diagnostic accuracy rate of 95.45 %, 75 %, 96.55 % and 93% respectively. When white blood count (WBC) and CRP level were combined with HPE findings, its sensitivity, specificity and diagnostic accuracy rate were 100%, 80% and 93.83 % respectively. Conclusions: CRP improves the diagnostic accuracy of Acute appendicitis. The adjunct use of CRP and leucocyte count can effectively reduce the negative appendectomy rate.